2017
DOI: 10.3390/ijms18010087
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Magnetic Nanoparticle-Labeled Chondrocytes Cultivated on a Type II Collagen–Chitosan/Poly(Lactic-co-Glycolic) Acid Biphasic Scaffold

Abstract: Chondral or osteochondral defects are still controversial problems in orthopedics. Here, chondrocytes labeled with magnetic nanoparticles were cultivated on a biphasic, type II collagen-chitosan/poly(lactic-co-glycolic acid) scaffold in an attempt to develop cultures with trackable cells exhibiting growth, differentiation, and regeneration. Rabbit chondrocytes were labeled with magnetic nanoparticles and characterized by scanning electron microscopy (SEM), transmission electron (TEM) microscopy, and gene and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…CS also interacts with collagen via electrostatic interactions between abundant amino groups and sulfo groups [90], and freeze-dried type 2 collagen-CS hybrid scaffold possesses improved stiffness in comparison to single component scaffolds, with a good porous structure resembling cartilage [91]. Moreover, type II collagen-CS scaffolds were also combined in the bi-layered scaffold with poly(lactic-co-glycolic acid) (PLGA) to further increase the mechanical and functional properties of biocomposites for cartilage regeneration [92]. CS-silk fibroin blends have also shown potential in cartilage regeneration [93,94].…”
Section: Cartilagementioning
confidence: 99%
“…CS also interacts with collagen via electrostatic interactions between abundant amino groups and sulfo groups [90], and freeze-dried type 2 collagen-CS hybrid scaffold possesses improved stiffness in comparison to single component scaffolds, with a good porous structure resembling cartilage [91]. Moreover, type II collagen-CS scaffolds were also combined in the bi-layered scaffold with poly(lactic-co-glycolic acid) (PLGA) to further increase the mechanical and functional properties of biocomposites for cartilage regeneration [92]. CS-silk fibroin blends have also shown potential in cartilage regeneration [93,94].…”
Section: Cartilagementioning
confidence: 99%
“…A material with adequate characteristics for cartilage engineering is chitosan, a polycationic polysaccharide that can be degraded enzymatically by the lysozyme Therapeutic Potential of Articular Cartilage Regeneration using Tissue Engineering Based… DOI: http://dx.doi.org /10.5772/intechopen.84697 present in the MEC of human cartilage. Chitosan has a chemical similarity with GAGs, which gives it the ability to interact with them [82]; through various in vitro studies, it has been demonstrated that scaffolds based on chitosan especially in combination with other biomaterials such as collagen II [108], hyaluronic acid [83], or fibroin [84] promote chondrogenic activity and support the production of aggrecan and type II collagen, thus improving cartilage repair [108].…”
Section: Carbohydrate-based Polymersmentioning
confidence: 99%
“…The material properties, degradation rates, and tissue compatibility of PLA can be modified by copolymerization with other monomers, resulting in copolymers such as poly (lactic acid-co-caprolactone) (PLGA), poly (lactic acid-co-caprolactone) (PLCL), poly (lactic acid-co-ethylene glycol) (PLEG), and poly (lactic acid-co-glutamic acid) (PLGM); this makes them biomaterials with highly adaptable properties for broad biomedical applications (Table 1) [108,110,[113][114][115].…”
Section: Synthetic Polymer-based Biomaterialsmentioning
confidence: 99%
“…Different pure or chemically modified synthetic polymers have already been used for tissue engineering applications, such as polycaprolactone for bone (Fedore, Tse, Nam, Barton, & Hatch, ; Groppo et al, ; Xue et al, ) or acrylonitrile butadiene styrene for tendon (Mozdzen, Rodgers, Banks, Bailey, & Harley, ) and skin (Cai, Azangwe, & Shepherd, ) tissue repair. Poly(lactic acid) (PLA) is another frequently used polymer for vascular (Tung, Chang, Ju, & Wang, ), cartilage (Revati et al, ; Su, Chen, Chen, & Chen, ), or bone (Du et al, ; Hao, Jiang, Jiang, Wang, & Wang, ; Lu, Dong, Zhang, Liu, & Wang, ; Zhao et al, ) applications. It displays favorable printing properties such as a low glass transition temperature (50–60°C) and it does not require a heated printing bed.…”
Section: Introductionmentioning
confidence: 99%